2017
DOI: 10.1136/bmjophth-2016-000057
|View full text |Cite
|
Sign up to set email alerts
|

Vitreoretinal interface abnormalities in middle-aged adults with visual impairment in the UK Biobank study: prevalence, impact on visual acuity and associations

Abstract: ObjectiveThe aim of this study was to determine the prevalence of vitreoretinal interface abnormalities (VRIA), the degree of visual impairment and associations with VRIA among adults, aged 40–69 years, in the UK Biobank study.Methods and analysisColour fundus photographs and spectral domain optical coherence tomography images were graded for 25% of the 8359 UK Biobank participants with mild visual impairment or worse (LogMAR >0.3 or Snellen <6/12) in at least one eye. The prevalence and contribution of VRIA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The prevalence of visual-impairing vitreoretinal interface abnormalities in our study (1.0%) was higher than that in the Hong Kong study (0.05%), 30 but lower than that in the UK Biobank Study (3.6%). 31 As the incidence of vitreoretinal interface abnormalities increase with age, 32 future population-based studies must include this as a potential cause of visual impairment among the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of visual-impairing vitreoretinal interface abnormalities in our study (1.0%) was higher than that in the Hong Kong study (0.05%), 30 but lower than that in the UK Biobank Study (3.6%). 31 As the incidence of vitreoretinal interface abnormalities increase with age, 32 future population-based studies must include this as a potential cause of visual impairment among the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Potential risk factors were selected based on a literature search or those related to putative mechanisms proposed by the study team, they included age, sex, 7 body mass index (BMI; kg/m 2 )), smoking, 19 hypertension, spherical equivalent, 20 visual acuity, 21 plasma high-density lipoprotein (HDL)-cholesterol, triglycerides, HbA1c 22 and cataract. 11 HbA1c, triglycerides and HDL were measured on blood samples collected at the health assessment.…”
Section: Covariate Selection and Categorisationmentioning
confidence: 99%
“…The BMES reported findings, similar to those in the BDES [ 59 ], whilst the NICOLA Study which included younger participants (mean age = 62 years) reported lower prevalences of VMA (22.6%), VMT (0.5%), ERM (7.6%), and macular holes (0.3%) [ 68 ]. Similarly, the UK Biobank study reported a 3.6% prevalence of VMI changes (in 55–66 year olds), with increasing age, female sex and Asian ethnicity as significant associations [ 30 ]. The study by Zapata et al [ 69 ] included participants aged 45 years and older and reported a lower prevalence of vitreoretinal interface abnormalities [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Beaver Dam Eye Study (BDES) recently reported the population prevalence of VMI abnormalities (VMIA) in participants aged 63 years and older [ 29 ]. McKibbin et al [ 30 ] reported on VMI grading on OCT in 25% of 8359 (2090) participants with visual impairment (VI) (in at least one eye) in the UK Biobank study (aged 54–66 years), which included 374 (4.9%), 73 (4.4%), and 22 (5.3%) Black or Black British controls without VI, participants with VI without vitreoretinal interface abnormalities (VRIA), and those with VI and VRIA, respectively [ 30 ].…”
Section: Introductionmentioning
confidence: 99%